Kebijakan Penegakan Hukum terhadap Tindak Pidana Terorisme yang Dilakukan Kelompok Radikal - Yasir Ahmadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Terrorism criminal has been thriven in Indonesia which can be threatened security in national or international scale. Because of that, Densus 88 AT Polri is given authority to take under control it. Law enforcemet of terrorism criminal needs to be solved integrally, planned and sustainable which is not only approached by penal solving but also solved by punishment the criminal. People should be realized that terrorism is threating thw wholeness and unity of Indonesa. The role of religion leader or society could actively play to enhance conscious and knowledge about nationality, so it can always responsive and alert to the movement of radical groups that developed in the area around.